Analisis Gaya Berpikir Sekuensial-Acak Konkret dalam Menyelesaikan Masalah Fisika - Sanusi, Dirgah Kaso (MACCA : Science-Edu Journal, 2025)
This study aims to describe the Concrete Sequential and Concrete Random thinking styles in solving physics problems of students. The subjects of this study were selected based on purposive sampling technique and two students of MAN 2 Makassar were selected, each of which represents the thinking style. The subjects were classified based on the thinking style questionnaire adapted from John Parks' instrument. This research used a qualitative descriptive approach. The data in this study were collected through problem solving tests and interviews as a form of clarification of the test results obtained. The results showed that students with Concrete Sequential thinking style relied more on memorized notes and equations to solve problems. Meanwhile, students with a Concrete Random thinking style do not fully understand the basic concepts and tend to use a trial and error approach.